Peri-implantitis and Severity Level - Elemek, Eser; Agrali, Omer Birkan; Kuru, Bahar; Kuru, Leyla (European Journal of Dentistry, 2020)
Objectives Different diagnostic criteria were used for diagnosis of peri-implant diseases. The aim of this cross-sectional study was to explore prevalence of peri-implant diseases and subclassify peri-implantitis based on different levels of radiographic and clinical findings.Materials and Methods Two hundred patients having 655 dental implants were included in this study. In addition to clinical measurements, standard long-cone parallel technique was used to evaluate marginal bone level around implants. Following diagnosis of peri-implant diseases, peri-implantitis was further subclassified using a severity leveling in terms of marginal bone level and probing depth.Results Mean age of 200 subjects was 52.8 ± 12.2 years and 63% were females. In total, bleeding on probing was present in 93% and suppuration in 27% of implants. On subject basis, 2.5% were diagnosed as healthy, 28% with peri-implant mucositis (PM), and 69.5% with peri-implantitis, whereas on implant basis, 3.6% were healthy, 36% presented PM, and 60.4% peri-implantitis. Furthermore, when severity leveling was applied, peri-implantitis prevalence changed markedly and ranged from 14.5 to 31.0% at the subject level and from 10.0 to 22.0% at the implant level. Subgingival restoration margins were observed in 70.6% of patients for implants with PM and in 44% patients for implants with peri-implantitis. Most of the implants with peri-implantitis were with platform match (71.5%).Conclusions Applying different thresholds to the peri-implantitis definition yielded different prevalence rates ranging from 10 to 31%. As no established diagnostic criteria are being used today, results from clinical studies may not reflect the true disease prevalence.
Keywords: marginal bone level; peri-implant disease; peri-implantitis